2016
DOI: 10.24059/olj.v20i2.614
|View full text |Cite
|
Sign up to set email alerts
|

Information Sharing, Community Development, and Deindividuation in the eLearning Domain

Abstract: In a study of the information behaviors of graduate students enrolled in an online Masters of Library and Information Science (MLIS) program, it was determined that learners engage in threaded discussions not only for cognitive purposes but for affective reasons as well. The information sharing among students was particularly prolific during a session in which medical ailments and information were discussed. Data were collected from an asynchronous class in a graduate LIS program, and were examined through lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The input of peers encourages members to continue participating in the group. Interactions increase the sense of community felt by students, and in turn, this sense of community encourages more interaction (Cooke, 2016).…”
Section: Peer Influencementioning
confidence: 99%
“…The input of peers encourages members to continue participating in the group. Interactions increase the sense of community felt by students, and in turn, this sense of community encourages more interaction (Cooke, 2016).…”
Section: Peer Influencementioning
confidence: 99%
“…Showing of openness to others through sharing personal information, beliefs and values are types of affective expressions that shows teachers' immediacy in online learning environment [7]. Therefore, affective sharing was the essential components of learning community in which the participants enjoy high level of respect and trust [19] which foster students social presence.…”
Section: Social Sharingmentioning
confidence: 99%
“…Building on the importance of resources in engagement, several authors have suggested that engagement can be enhanced by effective design and use of learning resources, particularly in the world of online learning 11,12 . Claxton 13 observed that, in order to be engaging, learning resources need to meet certain criteria.…”
Section: Introductionmentioning
confidence: 99%